The Slav Avant-garde in Australian Art - Bojić , Zoja (Poznańskie Studia Slawistyczne, 2020)
Australian art history includes a peculiar short period during which the European avant-garde values were brought to Australia by a group of Slav artists who gathered in Adelaide in 1950. They were brothers Voitre (1919–1999) and Dušan Marek (1926–1993) from Bohemia, Władysław (1918–1999) and Ludwik Dutkiewicz (1921–2008) from Poland, and Stanislaus (Stanislav, Stan) Rapotec (1911–1997) from Yugoslavia, later joined by Joseph Stanislaus Ostoja-Kotkowski (1922–1994) from Poland. Each of these artists went on to leave their individual mark on the overall Australian art practice. This brief moment of the artists’ working and exhibiting together also enriched their later individual work with the very idea of a common Slav cultural memory.